An MBSE Methodology for Capability Systems Definition. Issue 1 (July 2017) - Do, Quoc; Hartigan, Daniel
Abstract: Systems Engineering provides a structured means to define, design, implement, integrate, sustain and manage numerous interdependencies throughout the Lifecycle of complex systems. This paper presents a Model‐Based Systems Engineering (MBSE) methodology that focuses on the early Concept stage of the ISO/IEC/IEEE 15288:2015 to define the systems capability in the operational domain, functional domain and solution‐independent physical domain. The methodology consists of systemic processes that are governed by an information‐centric schema as well as enabling systems language and tools. The schema focuses on the objective information required during the capability design process to inform key design decisions and achieve convergence from conflicting stakeholder viewpoints. The paper opens with an introduction to MBSE and systems capability definition. Then, the detail of the methodology is discussed followed by an application of this approach to the Battlespace Communication Support Centre (BCSC) capability as a case study – reporting on the efficacy, lessons learned and recommendations for future applications.